Reversible uptake of sulfur-containing gases by single crystals of a Cr8 metallacrown. Issue 35 (14th August 2019) - Vitórica-Yrezábal, Iñigo J.; Sava, Daniel Florin; Reta, Daniel; Timco, Grigore A.; Winpenny, Richard E. P.
Abstract : The exposure of green crystals of the [CrF(O2 C t Bu)2 ]8 Cr 8 metallacrown to SO2 and H2 S gases results in the binding of the gas molecules in the internal molecular cavity, despite the absence of any pores or channels in the structure. Abstract : The exposure of green crystals of the [CrF(O2 C t Bu)2 ]8 Cr8 metallacrown to SO2 and H2 S gases results in the binding of the gas molecules in the internal molecular cavity, despite the absence of any pores or channels in the structure. Single crystal X-ray diffraction studies show that the gas molecules bind weakly to the bridging fluoride ligands. The desorption process was followed by TGA, DSC and in situ variable temperature single crystal X-ray diffraction, obtaining the gas binding energies for the gas guest molecules. These results are supported by DFT calculations.